Comparison of vaginal hysterectomy and laparoscopic hysterectomy: a systematic review and meta-analysis - Seung Hyun Lee; So Ra Oh; Yeon Jean Cho; Myoungseok Han; Jung-Woo Park; Su Jin Kim; Jeong Hye Yun; Sun Yi Choe; Joong Sub Choi; Jong Woon Bae (BMC Women's Health, 2019)
Abstract Background There are various surgical approaches of hysterectomy for benign indications. This study aimed to compare vaginal hysterectomy (VH) and laparoscopic hysterectomy (LH) with respect to their complications and operative outcomes. Methods We selected randomised controlled trials that compared VH with LH for benign gynaecological indications. We included studies published after January 2000 in the following databases: Medline, EMBASE, and CENTRAL (The Cochrane Library). The primary outcome was comparison of the complication rate. The secondary outcomes were comparisons of operating time, blood loss, intraoperative conversion, postoperative pain, length of hospital stay and duration of recuperation. We used Review Manager 5.3 software to perform the meta-analysis. Results Eighteen studies of 1618 patients met the inclusion criteria. The meta-analysis showed no differences in overall complications, intraoperative conversion, postoperative pain on the day of surgery and at 48 h, length of hospital stay and recuperation time between VH and LH. VH was associated with a shorter operating time and lower postoperative pain at 24 h than LH. Conclusions When both surgical approaches are feasible, VH should remain the surgery of choice for benign hysterectomy.